Biological Activities of Oleanolic Acid Derivatives from Calendula officinalis Seeds. (16th February 2016) - Zaki, Ahmed; Ashour, Ahmed; Mira, Amira; Kishikawa, Asuka; Nakagawa, Toshinori; Zhu, Qinchang; Shimizu, Kuniyoshi
Abstract : Phytochemical examination of butanol fraction of Calendula officinalis seeds led to the isolation of two compounds identified as 28‐ O ‐β‐D‐glucopyranosyl‐oleanolic acid 3‐ O ‐β‐D–glucopyranosyl (1→3)‐β‐D‐glucopyranosiduronic acid (CS1) and oleanolic acid 3‐ O ‐β‐D–glucopyranosyl (1→3)‐β‐D‐glucopyranosiduronic acid (CS2). Biological evaluation was carried out for these two compounds such as melanin biosynthesis inhibitory, hyaluronic acid production activities, anti obesity using lipase inhibition and adipocyte differentiation as well as evaluation of the protective effect against hydrogen peroxide induced neurotoxicity in neuro‐2A cells. The results showed that, compound CS2 has a melanin biosynthesis stimulatory activity; however, compound CS1 has a potent stimulatory effect for the production of hyaluronic acid on normal human dermal fibroblast from adult (NHDF‐Ad). Both compounds did not show any inhibitory effect on both lipase and adipocyte differentiation. Compound CS2 could protect neuro‐2A cells and increased cell viability against H2 O2 . These activities (melanin biosynthesis stimulatory and protective effect against H2 O2 of CS2 and hyaluronic acid productive activities of these triterpene derivatives) have been reported for the first time. Copyright © 2016 John Wiley & Sons, Ltd.